PENGARUH LATAR BELAKANG PENDIDIKAN MAHASISWA BARU DALAM PENYERAPAN ILMU AKUNTANSI DI STAIN JURAI SIWO METRO - Yoesoef, Fatullah (P3M STAIN Jurai Siwo Metro, 2013)
Learning accounting serves to develop the knowledge, skills, attitudes rational, conscientious, honest, and accountable through the procedure of recording, classifying, financial transactions, then Accounting is an art rather than the science of recording, classifying and summarizing the events and events at least partially finance the rigorous way and with the instructions or expressed in money, and so the interpretation of accounting education should produce a professional accountant in line with the need for accounting services in the next century. Higher education does not produce an accounting professional as accountant certainly will not be sold on the labor market.Â Keywords: Influence, eductional background, and accountingÂ